2000
DOI: 10.1017/s0007114500000301
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial influence of an indigenous low-iron diet on serum indicators of iron status in patients with chronic liver disease

Abstract: The main Fe storage organ in the body is the liver. In patients with chronic liver disease, secondary Fe overload is common. Phlebotomy, often used in the West to reduce Fe overload to improve the efficacy of interferon therapy, is not socially acceptable in India. We assessed the efficacy of a low-Fe diet in reducing serum Fe levels. Nineteen patients with hepatitis B-and C-related chronic liver disease, ten with normal (Ͻ 25 mol/l) baseline serum Fe levels (group A) and nine with high (Ͼ 25 mol/l) serum Fe l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…1). Similar to our findings, a recent study from India (14) has shown that a lowiron diet for 4 months led to significant reductions in both transaminase activities and iron parameters in patients with hepatitis B-or C-related chronic liver diseases. Though (17,20,21 …”
Section: ( Al T ) V a L U E F O L L O Wi N G P H L E B O T O My T O Psupporting
confidence: 92%
“…1). Similar to our findings, a recent study from India (14) has shown that a lowiron diet for 4 months led to significant reductions in both transaminase activities and iron parameters in patients with hepatitis B-or C-related chronic liver diseases. Though (17,20,21 …”
Section: ( Al T ) V a L U E F O L L O Wi N G P H L E B O T O My T O Psupporting
confidence: 92%
“…In addition, iron deposits in the liver were associated with high activity and severity of hepatitis B 17 . Furthermore, consumption of a low‐iron diet has been found to reduce alanine transaminase levels in patients with HBV infection 18 …”
Section: Discussionmentioning
confidence: 99%
“…Tandon et al have recently shown that a special low‐iron vegetarian diet was able to significantly reduce the serum iron and ferritin levels ( Table 3). 22 The reduction in the iron parameters was proportionally greater in patients who had higher baseline serum iron and ferritin levels.…”
Section: Iron Reduction Therapymentioning
confidence: 92%